Analisis Faktor-Faktor Yang Mempengaruhi Indeks Pembangunan Manusia Di Wilayah Gerbangkertosusila Plus Periode Tahun 2016-2020 - Resa Aji Pangestu (Jurnal Ilmu Ekonomi, 2022)
This study aims to determine the factors that influence the human development index in the Gerbangkertosusila Plus area of East Java Province. This study uses a quantitative descriptive method and the variables used in this study are economies, population, poverty, and special allocation funds in the gate area of ​​kertosusila plus. The data used in this study were obtained from BPS East Java Province. The results of this study indicate that the per capita GRDP has a positive effect, population density has a negative effect, the number of poor people has a negative effect, the special allocation fund for education has a positive effect and the special allocation fund for health has a negative effect on the human development index in the Gerbangkertosusila Plus area.